2016
DOI: 10.1002/jmri.25373
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted MRI abnormalities in an outbreak ofStreptococcus agalactiaeSerotype III, multilocus sequence type 283 meningitis

Abstract: 4 J. Magn. Reson. Imaging 2017;45:507-514.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…and served as a side dish with porridge by food stalls within larger eating establishments. Persons with severe clinical cases had meningoencephalitis, bacteremia, and septic arthritis ( 2 4 ). GBS, or Streptococcus agalactiae , was identified as the causative agent ( 2 , 3 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…and served as a side dish with porridge by food stalls within larger eating establishments. Persons with severe clinical cases had meningoencephalitis, bacteremia, and septic arthritis ( 2 4 ). GBS, or Streptococcus agalactiae , was identified as the causative agent ( 2 , 3 ).…”
mentioning
confidence: 99%
“…GBS is found in ≈30% of healthy adults ( 5 ) and is a member of the human commensal gastrointestinal and genitourinary flora ( 4 ). GBS is a common cause of neonatal sepsis, is acquired by newborns from the vaginal flora of the mother, and is an increasingly common pathogen among vulnerable populations ( 6 ).…”
mentioning
confidence: 99%
“…This finding was comparable to various studies that also reported similar associations between GBS infections and bacteraemia. (8,19,22) In addition, our results showed that patients with GBS septic arthritis were more likely to have significantly higher CRP values, with 95.2% of these patients having CRP > 150 mg/L. In contrast, only 71.0% of patients with septic arthritis from non-GBS microorganisms had CRP > 150 mg/L on univariate analysis (p = 0.017).…”
Section: Discussionmentioning
confidence: 60%
“…Invasive GBS infections in healthy adults are not as common compared to severe infections in pregnant women, neonates, the elderly and immunocompromised individuals. (5,12,(14)(15)(16)(17)(18)(19) Previous studies have described GBS causing bovine mastitis (20) and disease in fish. (21) However, our understanding of the links between the routes and likelihood of interspecies transmission and invasive disease in humans remains lacking.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that consumption of fish is associated with an increased risk of GBS colonization in people (Foxman et al, 2007 ). In 2015, an outbreak of GBS infection was related to consuming infected raw freshwater fish, which affected more than 200 patients in Singapore (Tan et al, 2017 ). Thus, it is proposed that some strains of aquatic GBS may present a zoonotic or anthroponotic hazard and the fish may be a reservoir of pathogenic GBS.…”
Section: Introductionmentioning
confidence: 99%